Penentuan Premi Tahunan Asuransi Jiwa Syariah Dwiguna Gabungan Berjangka n-Tahun - Samsinar Samsinar; Darma Ekawati; Ahmad Ansar (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2023)
Sharia life insurance is an effort to help each other among customers by paying tabarru funds intended for customers who are at risk of unexpected financial losses caused by death. The purpose of this research is to determine the annual premium value of the combined -year endowment life insurance based on sharia principles with the interest rate changed to Return On Investment (ROI) which changes stochastically following the Langevin type model and obtains the ROI relationship, the term of the agreement, the amount of compensation for the annual premium of the sharia -year combined endowment term life insurance. The Monte-Carlo simulation method is applied to obtain annual premium values ​​with initial ROI values ​​equal to 0.35, 0.06 and 0.029. The results obtained in this study by applying a Monte-Carlo simulation to the calculation of the annual sharia -year joint endowment life insurance premium for joint participants are men aged 45 years, women aged 42 years, and men aged 18 years and older. A 10-year agreement with an initial ROI value of 0.35 is Rp. 6,161,275, an initial ROI value of 0.06 is Rp. 6,585,471, and an initial ROI value of 0.029 is Rp. 6,631,190. The results obtained show that the relationship between ROI, the term of the agreement and the amount of compensation for the annual endowment life insurance premium is that the smaller the initial ROI value, the greater the annual premium value.